2019
DOI: 10.7717/peerj.7023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effects of different mesenchymal stem cells on rheumatoid arthritis in mice

Abstract: Background Rheumatoid arthritis (RA) is a chronic and nonspecific autoimmune disease, which leads to joint destruction and deformity. To investigate the potential of human mesenchymal stem cells (MSCs) as a new therapeutic strategy for patients with RA, we compared the therapeutic effects of bone marrow derived MSCs (BMSCs), umbilical cord derived MSCs (UCs), and stem cells derived from human exfoliated deciduous teeth (SHED) on collagen-induced arthritis (CIA) in mice. Methods A total of 24 DBA/1 mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 56 publications
(68 reference statements)
2
35
0
1
Order By: Relevance
“…Besides, BMSCs also applied to treat chronic inflammatory diseases [136,137]. A comparative study showed that the systemic infusion of BMSCs significantly improved symptoms of RA in mice [138]. BMSCs reduced bone erosions, synovitis and articular destruction, levels of TNF-α and IL-1β in serum and joint, which results in an improvement of inflammation state in RA mice.…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, BMSCs also applied to treat chronic inflammatory diseases [136,137]. A comparative study showed that the systemic infusion of BMSCs significantly improved symptoms of RA in mice [138]. BMSCs reduced bone erosions, synovitis and articular destruction, levels of TNF-α and IL-1β in serum and joint, which results in an improvement of inflammation state in RA mice.…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…BMSCs reduced bone erosions, synovitis and articular destruction, levels of TNF-α and IL-1β in serum and joint, which results in an improvement of inflammation state in RA mice. BMSCs are considered to be the best stem cells for the treatment of RA when compared to UCSCs and exfoliated deciduous teeth stem cells [138]. In addition, a randomized, triple-blind trial showed the improvement of Western Ontario and McMaster Universities Arthritis Index (WOMAC), visual analog scale (VAS), time to jelling, pain-free walking distance, and standing time in 30 RA patients treated with BMSCs [139].…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…By far, the most prevalent source of MSCs is adult bone marrow (BM), followed by adipose tissue and, more recently, umbilical cord either from whole tissue or more specifically from umbilical cord blood (UC) [ 48 , 49 , 50 ]. Of late, MSCs have been isolated from alternative tissues [ 51 ], such as gingiva [ 52 , 53 ], amniotic fluid [ 54 , 55 ], placenta [ 56 ], synovial fluid or membrane [ 57 ], and nasal tissues ( ; patent number: WO2019022386, [ 58 , 59 ]). In all instances, the expanded MSCs matched with the minimal criteria defined by the International Society for Cellular Therapy (ISCT) [ 60 ] and have demonstrated similar efficacy in ameliorating experimental arthritis [ 47 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…An in vivo study indicated that treatment with MSCs obtained from different sources (bone marrow, umbilical cord, or human exfoliated deciduous teeth) in a mouse model of collagen-induced arthritis significantly improved bone erosions, synovitis, and articular destruction [304]. This improvement of clinical symptoms was paralleled by reduced levels of the pro-inflammatory cytokines TNF-α and IL-1β both in serum and joints [304].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%